2016
DOI: 10.3390/nu8080452
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Casein Protein Prior to Sleep on Fat Metabolism in Obese Men

Abstract: We have previously shown that ingesting protein at night before sleep is either beneficial or non-detrimental to metabolism, health, and body composition in obese women. However, the overnight protein-induced lipolytic actions and mechanism for improved metabolism and body composition have not been fully established. Therefore, in a crossover design, twelve obese men (age, 27.0 ± 2.2 years) were randomly assigned to ingest (within 30 min of sleep) casein protein (CAS, 120 kcal) or a non-nutritive placebo (PLA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
33
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 46 publications
6
33
1
Order By: Relevance
“…In theory, the discrepant findings between past (6)(7)(8)(9) and present investigations of bedtime snack ingestion and next morning metabolism also may relate to the characteristics of recruited participants. Diet-induced thermogenesis has been reported to be greater in lean v. obese males (28) , which implies that bedtime snack ingestion confers a greater potential to increase next morning RMR in lean compared with obese males.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…In theory, the discrepant findings between past (6)(7)(8)(9) and present investigations of bedtime snack ingestion and next morning metabolism also may relate to the characteristics of recruited participants. Diet-induced thermogenesis has been reported to be greater in lean v. obese males (28) , which implies that bedtime snack ingestion confers a greater potential to increase next morning RMR in lean compared with obese males.…”
Section: Discussioncontrasting
confidence: 57%
“…The treatment condition containing 10 g of protein (BS10) was chosen to mimic the approximate amount of protein in a typical glass of milk. The treatment with the highest amount of protein (BS30) was chosen to meet the 30 g protein threshold postulated to be required to suppress appetite (18) and to match the protein dose administered in previous bedtime snack studies (6)(7)(8)(9) . Participants were given an empty bottle for BS0 and filled it with 400 ml of tap water to be consumed at the time of the bedtime beverage.…”
Section: Bedtime Beverage Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a study by Lay and colleagues failed to observe an increase in RMR when a pre-sleep snack was consumed~10 h earlier in mildly overweight young men [40]. These findings were confirmed by Kinsey et al, who reported no increase in RMR~8 h post bedtime snack consumption in obese young men [56]. The absence of any changes in next-morning RMR is not surprising as previous metabolic ward investigations have demonstrated that diet-induced thermogenesis returns to basal values within six hours of consuming a pre-sleep snack [58].…”
Section: Discussionmentioning
confidence: 84%
“…However, we were unable to detect any differences between treatment groups for the aforementioned variables. Studies investigating the effects of a pre-sleep snack on next-morning RMR measurements are equivocal, with some showing an increase [36] and others no effect [40,56,57]. Discrepancies in these findings are likely related to the elapsed time between pre-sleep snack consumption and RMR measurement, with shorter time-frames increasing the likelihood of finding an effect.…”
Section: Discussionmentioning
confidence: 99%